Physiological and metabolic responses of Parabadminton athletes to field simulated effort - Oliveira, S. F.; Oliveira, J. I.; Winckler, C.; Lourenço, T. F.; Haiachi, M. C.; Felder, H. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Due to the increase in the number of Parabadminton (PBd) athletes and the lack of scientific knowledge of the sport, it is important to evaluate performance variables in different game stimuli. Thus, this study sought to examine the physiological and metabolic responses in a simulated effort protocol in PBd athletes. METHODS: Forty-seven volunteers (WH1=7; WH2=9; SL3=8; SL4=9; SU5=6; SH6=8) performed a simulated effort protocol, consisting of 2 blocks of activities (1st change of direction + 1st simulated effort; 2nd change of direction + 2nd simulated effort). Peak and average oxygen consumption (VO2peak and VO2avg), peak, percentage, and average heart rate (HRmax, %HRmax, and HRavg), percentage of carbohydrates and lipids contributions (%CARB and %FAT), and average and total energy expenditure (EEavg and EEtotal) were evaluated. The data was compared between protocol stages, functional classes (FCs), and court size. It was adopted P<0.05. RESULTS: Differences were found between the stages of the protocol in VO2peak (P=0.0008), VO2avg (P=0.0004); HRmax (P<0.0001); %HRmax (P=0.0001), HRavg (P=0.0001), %CARB (P=0.0001), %FAT (P=0.0001), EEavg (P=0.0002), and EEtotal (P=0.008). Among FCs, SL4 athletes were superior to WH1 athletes for VO2peak (P=0.075), VO2avg (P=0.022), EEavg (P=0.011), and EEtotal (P=0.022). Athletes who completed protocol in the full court were greater than half court for VO2peak (P<0.001), VO2avg (P<0.001), %HRmax (P=0.032), HRavg (P=0.018), %CARB (P=0.022), %FAT (P=0.022), and EEavg (P=0.016). CONCLUSIONS: PBd athletes belonging to higher FCs (4, 5, and 6) and who cover greater distances on the court exhibit physiological and metabolic responses under greater influence of the type of disability.